Knowledge of man about breastfeeding - Sâmia Jamylle Santos de Azevedo; Flávia Andrea Pereira Soares dos Santos; Caroline Evelin Nascimento Kluczynik Vieira; Larissa Soares Mariz; Aylla Nauanna da Silva; Bertha Cruz Enders (Acta Scientiarum. Health Sciences, 2016)
The male participation in the process of breastfeeding needs to be encouraged as it can contribute significantly to the prevention of early weaning. In this sense, this research aimed to identify a parent's knowledge about breastfeeding. This is an exploratory and descriptive study with a qualitative approach, performed in the Family Health Strategy in Bom Jesus, Rio Grande do Norte State, Brazil. Data were collected through semi-structured interview with the guiding question: what is your understanding of breastfeeding? The population was 15 men with aged over 18 years old and preserved mental faculties, who lived with his wife and the child under one year of age and performed development and growth consultations in the Family Health Strategy. The interviews were conducted in place previously defined parent. The information was organized as content analysis Bardin, giving rise to two categories and analyzed according to the symbolic interacionism. It was observed that parents of participating antenatal clinics have more knowledge about it and recognize the benefits of breastfeeding in this way can encourage their wives in order to exclusive breastfeeding.